Igniting Determinants Of Tourism Service Purchase Decisions - Hidayat, Candra; Triono, Freddy; Haryono, Joko; Pangkerego, Eduard Rudolf (International Journal of Artificial Intelligence Research, 2025)
This research aims to analyze the influence of promotion and price on purchasing decisions for tourism services in Lawangsewu, Semarang. This research employed quantitative methods with regression analysis. The author used primary data and purposive sampling, resulting in a sample size of 95 respondents. Partial Least Squares (PLS) analysis was used for this research. The data analysis revealed that promotion and price significantly influence purchasing decisions for tourism services in Lawangsewu, Semarang. Future researchers investigating related issues can use this study's findings as a guide. This study can also be used as assessment data to help business managers focus more on promotions to facilitate marketing campaigns with a wider audience.